2013
DOI: 10.7860/jcdr/2013/6283.3843
|View full text |Cite
|
Sign up to set email alerts
|

Oral Rinse as a Simpler Approach to Exfoliative Cytology: A Comparative Study

Abstract: IntrOductIOnBiopsy is the diagnostic test of choice for oral potentially malignant disorders and malignant lesions.But since scalpel biopsy is an invasive procedure associated with potential morbidity,several adjunctive screening aids are used to assist clinicians with the detection of early cancerous changes [1]. Although oral exfoliative cytology is a simple non-invasive technique, the traditional exfoliative cytology methods show low sensitivity (i.e. a high proportion of false negatives), inadequate sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Since then, exfoliative cytology has gained a widespread use, not only confined to gynecologic endocrinology but also to other various departments including that of oral cancer detection and in early diagnosis of Acquired Immunodeficiency Syndrome (AIDS). [5][6][7][8] Many techniques have been employed for collecting the exfoliated cells of the oral mucosa like oral rinse technique, scraping the oral mucosa by means of a steel spatula, wooden tongue depressor, and oral CDX brushes 9 . In the present study, wooden tongue depressor was used as it is easy to use, disposable, leads to good amount of exfoliated sample collection and even distribution of obtained sample onto a glass slide.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, exfoliative cytology has gained a widespread use, not only confined to gynecologic endocrinology but also to other various departments including that of oral cancer detection and in early diagnosis of Acquired Immunodeficiency Syndrome (AIDS). [5][6][7][8] Many techniques have been employed for collecting the exfoliated cells of the oral mucosa like oral rinse technique, scraping the oral mucosa by means of a steel spatula, wooden tongue depressor, and oral CDX brushes 9 . In the present study, wooden tongue depressor was used as it is easy to use, disposable, leads to good amount of exfoliated sample collection and even distribution of obtained sample onto a glass slide.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] It is well-established that only a small percentage of the harvested epithelial cells obtained during conventional smear are transferred to the glass slide and there is always a possibility of potential source for false negative smears. [ 8 ] It is shown that a maximum of only 20% of the cells collected on a variety of collection devices can be mechanically transferred to the flat surface of a glass slide. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Shaila et al ., slides prepared by the conventional wooden spatula method in normal oral mucosa were disregarded due to either excessive clumping or scarcity of cells. [ 8 ] Ogden et al . found less cell yield and cell dispersion,[ 10 ] whereas Ahmed et al .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no universally agreed‐on method of oral sampling for the detection of HPV DNA. The most common method is using an oral rinse swirl or gargle to obtain an oral rinse sample, which is easy and non‐invasive suitable for oral screening . DNA can be extracted, and polymerase chain reaction (PCR) amplified after storage of mouthwash solution at room temperature for periods of up to 30 days .…”
Section: Introductionmentioning
confidence: 99%
“…The most common method is using an oral rinse swirl or gargle to obtain an oral rinse sample, which is easy and noninvasive suitable for oral screening. 1,[20][21][22] DNA can be extracted, and polymerase chain reaction (PCR) amplified after storage of mouthwash solution at room temperature for periods of up to 30 days. 23 However, the prevalence of HPV varies according to sample size, sampling methods 24 (probability or non-probability sampling methods), analysis, specimens (such as fresh, frozen, formalin-fixed paraffin-embedded samples with tissue/cell or plasma/ serum), and methodology (such as PCR and nested PCR using GP5+/6+ primer, PGMY09/11 primer MY09/11 with GP5+/6+ primer; Southern blotting assay; real-time PCR, DNA/RNA In situ hybridization; hybrid capture II; antibodies against early/late HPV protein; and DNA/RNA microarray).In this study, we investigated the prevalence of HPV infection in 594 oral rinse samples from healthy northern Thai population using PCR (GP5+/6+ primers) 25 and HPV genotyping by sequencing.Demographic data and behavioral factors for these subjects were collected and evaluated for association with HPV.…”
mentioning
confidence: 99%